2019
DOI: 10.37236/8623
|View full text |Cite
|
Sign up to set email alerts
|

Universality for Random Surfaces in Unconstrained Genus

Abstract: Starting from an arbitrary sequence of polygons whose total perimeter is $2n$, we can build an (oriented) surface by pairing their sides in a uniform fashion. Chmutov & Pittel have shown that, regardless of the configuration of polygons we started with, the degree sequence of the graph obtained this way is remarkably constant in total variation distance and converges towards a Poisson–Dirichlet partition as $n \to \infty$. We actually show that several other geometric properties of the graph are universal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 19 publications
(37 reference statements)
0
23
0
Order By: Relevance
“…The analogous result is known to hold for surfaces obtained by randomly gluing polygons together [23,15,12].…”
Section: Some Remarks About These Resultsmentioning
confidence: 62%
“…The analogous result is known to hold for surfaces obtained by randomly gluing polygons together [23,15,12].…”
Section: Some Remarks About These Resultsmentioning
confidence: 62%
“…Similar results have been obtained in [9] for permutations that are equicontinuous in both coordinates and converging as a permuton (see definitions there). With the motivation of random gluing of polygons, a stronger convergence (in total variation distance) was established in [4] when one of the permutations has all its cycles of length at least 3 (see also [5]) and in [3] when one of the permutations is an involution without fixed point. None of the previous results covers for example the product of two Ewens distributions.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In [20], Guth, Parlier and Young showed that both random triangulated surfaces and random hyperbolic surfaces have large total pants decomposition length. In [7], Budzinski, Curien and Petri computed the asymptotic diameter of a random triangulated surface with respect to the hyperbolic metric, while in [10], Budzinski, Curien and Petri computed the asymptotic minimal diamater of a hyperbolic surface, and these quantities simply differ by a factor of 2. These results suggest a close relationship between random triangulated surfaces and random hyperbolic surfaces.…”
Section: Introductionmentioning
confidence: 99%